Case Report: Extensive deep vein thrombosis and venous pseudoaneurysm following percutaneous transcatheter tricuspid valve intervention - Abood, Zaid; Jan, M. Fuad; Weiss, Eric S.; Bajwa, Tanvir; Allaqaband, Suhail Q.; Mewissen, Mark W. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionTranscatheter tricuspid valve intervention (TTVI) has evolved as a less-invasive alternative to surgical treatment of severe tricuspid regurgitation. Although venously delivered valves have been introduced, the risk of venous access site complications is unknown. We present a patient who suffered phlegmasia cerulea dolens post-TTVI.Case summaryWe present an 88-year-old female patient who developed phlegmasia cerulea dolens of the right lower extremity shortly after successful TTVI delivered through the right common femoral vein via a 35F sheath. Ipsilateral transpopliteal venography demonstrated an occlusive thrombus in the right common femoral vein and the incidental finding of an external iliac vein pseudoaneurysm. Endovascular treatment consisting of mechanical thrombectomy followed by adjunctive placement of self-expanding metallic stents resulted in restoration of iliofemoral venous outflow and excellent recovery with resolution of the patient's symptoms.ConclusionsSurveillance, e.g., duplex ultrasonography, immediately post-TTVI is important to rule out acute thrombosis of the venous access site and other complications associated with a large sheath.